Take filtering capability's nylon production reducing mechanism - LI CHUANSHENG (2017)
The utility model provides a take filtering capability's nylon production reducing mechanism, which comprises a support, set up quick -witted case on the frame, set up crushing roller around the machine incasement between the wall of both sides, the outer wall of machine case sets up the motor, the output of motor with crushing roller's one end is connected, the bottom of machine case sets up the discharge gate, crushing roller comprises a crushing roller, the 2nd crushing roller, the 3rd crushing roller and fourth crushing roller. The utility model discloses a consequently above -mentioned crushing roller's setting can improve kibbling efficiency so that the raw materials is fully crushing, and this kind sets up and has saved the space when mode is saved time, it is online that the arc can be stayed with some raw materialss of not smashing of quick -witted incasement to the arc net that sets up simultaneously, then fourth crushing roller can net accumulational bulk material with the arc and smashes repeatedl